PRODUCTION AND CHARACTERIZATION OF BIOSURFACTANT BY Pseudomonas fluorescens USING CASSAVA FLOUR WASTEWATER AS MEDIA - Venty Suryanti; Soerya Dewi Marliyana; Desi Suci Handayani; Desi Ratnaningrum (Universitas Gadjah Mada, 2013)
Biosurfactant with efficient emulsification properties could be produced by Pseudomonas flourescens using cassava flour wastewater (manipueira) as media. The ability of P. flourescens to produce biosurfactant could suggest potential use in industrial and environmental applications. Media containing a mixture of natural manipueira and nutrient broth with 48 h fermentation was the optimum condition for the biosurfactant production. Based on UV-Vis and FT-IR spectra, the biosurfactant was indicated as rhamnolipids containing hydroxyl, ester, carboxylic and aliphatic carbon chain functional groups. Biosurfactant exhibited critical micelle concentration (CMC) value of 715 mg/L and reduced the surface tension of the water from 80 mN/m to 59 mN/m. The biosurfactant was able to decrease the interfacial tension about 51-70% when benzyl chloride, palm oil and kerosene were used as water-immiscible compounds. The biosurfactant was able to form stable emulsion until 30 days when paraffin, soybean oil, lubricant oil and kerosene were used as water-immiscible compounds.